2020
DOI: 10.1016/j.clnu.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian diet and risk of gout in two separate prospective cohort studies

Abstract: Backgrounds & aims: Plant-based diets may target multiple pathways in gout pathogenesis (uric acid reduction and anti-inflammation) while improving gout associated cardiometabolic comorbidities. We aim to prospectively examine the relationship between a vegetarian diet and gout, and to explore if this relationship is independent of hyperuricemia. Methods: We followed 4903 participants in the Tzu Chi Health Study (Cohort1, recruited in 2007e2009) and 9032 participants in the Tzu Chi Vegetarian Study (Cohort2, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 49 publications
1
27
1
3
Order By: Relevance
“…Previously, it was thought that the avoidance of high-purine foods forms the single basis of an appropriate diet for patients with gout [46]. Studies have shown that purines from plants with a high purine content might potentially increase the risk of UA accumulation, but for the most part, high purine content is found in energy-rich animal meats, fish, and visceral organs such as the liver [47,48]. A recent cross-sectional study from China reported that the “animal products” pattern, characterized by a high intake of fish, fresh meat, animal giblets, and wheat products, was correlated with an increased prevalence of hyperuricemia [49].…”
Section: Dietary Factors and Risk For Hyperuricemiamentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, it was thought that the avoidance of high-purine foods forms the single basis of an appropriate diet for patients with gout [46]. Studies have shown that purines from plants with a high purine content might potentially increase the risk of UA accumulation, but for the most part, high purine content is found in energy-rich animal meats, fish, and visceral organs such as the liver [47,48]. A recent cross-sectional study from China reported that the “animal products” pattern, characterized by a high intake of fish, fresh meat, animal giblets, and wheat products, was correlated with an increased prevalence of hyperuricemia [49].…”
Section: Dietary Factors and Risk For Hyperuricemiamentioning
confidence: 99%
“…Soy protein may increase serum UA; however, the expected increase in response to amounts typically ingested by Asian people would almost certainly be clinically irrelevant [66]. In general, diets rich in plant foods were not found to be associated with an increased risk of hyperuricemia and gout, even when plant foods with high purine content such as soy legume products were consumed [48,51,71,72]. The British Society for Rheumatology, in their recommendations for the management of gout, recognized these recent findings and stated that inclusion of soybeans and vegetable sources of protein in the diet should be encouraged, but high-purine foods at the same time avoided [73].…”
Section: Dietary Factors and Risk For Hyperuricemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Gout is a kind of in ammatory arthritis caused by the monosodium urate(MSU) crystals deposited in joints and the surrounding soft tissues,which derives from long-standing hyperuricemia [1] .The course of gout include four stages:asymptomatic hyperuricemia,acute gouty arthritis,intercritical gout and chronic gouty arthritis [2] .Patients can suffer signi cantly attack mainly about the joint pain with sudden onset,fever,redness and swelling when acute gout episodes [3] .This process can affect the patient's quality of life seriously,even functional disability,therefore,gout aroused people's attention increasingly.Nevertheless,with the continuous improvement of people's dietary patterns and lifestyle,the prevalence of gout are on the increase remarkable [4] .A large number of epidemiological data showed that the prevalence of gout in the world is about 0.1-10% on average [5][6] .In western developed countries,there are 3-6% of men and 1-2% of women have gout [7] .There is evidenced that [8] the prevalence of gout is more than 1% in Japanese men who older than 30 years,and in China,there might be 2 per 100 inhabitants suffer from gout [9] . At present,the pathogenesis of gout is still in exploration.Previous studies have con rmed that environmental,diet and genetic factors play roles in the development and incidence of gout.For example,vegetarian diet can reduce the risk of gout in Taiwan by Chiu THT et al [10] .And from a genetic standpoint,substantial genome-wide association studies(GWAS), meta-analyses and case-control studies have found that ABCG2,PKD2,SLC2A9,KCNQ1,SLC22A12,SLC17A1,NLRP3 and so on gene polymorphism are in uence the susceptibility of gout [11][12] .Researchers also agreed that genetic factors are the main factors affecting the onset of gout.…”
Section: Introductionmentioning
confidence: 99%